A numerical investigation of freshwater and sediment discharge variations of Poyang Lake catchment, China over the last 1000 years. (September 2015) - Gao, Jian Hua; Xu, Xianan; Jia, Jianjun; Kettner, Albert J; Xing, Fei; Wang, Ya Ping; Yang, Yang; Qi, Shuhua; Liao, Fuqiang; Li, Jun; Bai, Fenglong; Zou, Xinqing; et al.
The Poyang Lake catchment, an important sub-catchment of Changjiang, experienced 'Little Ice Age' (LIA) and accelerating intensity of human activities during the last 1000 years. As such, the area and time period serve as a perfect case to study the variations in water and sediment discharge under combined natural and anthropogenic impact. Simulation results of the model HydroTrend indicate that the annual average cumulative water discharge of the five rivers entering Poyang Lake over the last 1000 years is 103.65 ± 1.80 km 3, and climate change is the dominating factor determining water discharge variations over time. Influenced by the LIA (AD 1451–1850), the total water discharge of the five rivers was reduced by 10%. Sediment load discharging into Poyang Lake by the five rivers was only 9.21 ± 0.43 Mt yr −1 between AD 1000 and 1700, when the anthropogenic impact on the landscape was still low. However, with the human activities accelerating during the past 300 years, the sediment load entering Poyang Lake underwent a drastic change. Because of intensified soil loss, the total sediment load entering Poyang Lake during AD 1800–1950 increased by 58.7%, compared with AD 1000–1700. After AD 1950, the sediment load variation is mainly reflected by the combined impact of dam emplacement and soil erosion. As sediment interception by dams continuously increased over time, the total sediment load entering Poyang Lake during AD 1990–2000 is only 60.9% of that of the highest riverine sediment flux during AD 1951–1980, which is almost equal to that of the lowest level during AD 1000–1700. The sediment load of many rivers in the world exhibited similar variation trends as that of Poyang Lake under combined impact of climate change and human activities. Better understanding the mechanisms of these variation trends is helpful to analyzing the formation and evolution of an estuary-shelf sedimentary system over the Holocene.